الصكوك الإسلامية كبديل تمويلي للعجز الموازني في الجزائر - بن دعاس، زهير; رقوب، نريمان (جامعة الشهيد حمه لخضر الوادي, 2018)
This search paper aims to put Islamic instruments as an alternative to traditional sources approved to finance the state budget, we have generally reached the limited mechanisms adopted by Algeria in the funding of its budget, which have made financial balances in recent years is very critical, because of the high pace of public expenditure with the sharp decline in oil prices since the second half of 2014, In front of this situation, Algeria must searching for the alternative sources of financing without oil revenues along the lines of Islamic instruments that have proved effective in many Islamic countries, where it can be used as a sources of financing to maintain the financial balance of the state, reduce budget deficit ,and attracting a large segment investors, which refuses to deal and employment interest rate known in advance.
تهدف هذه الدراسة إلى طرح الصكوك الإسلامية بأشكالها المختلفة كبديل للمصادر التقليدية المستخدمة في تمويل العجز الموازني في الجزائر، بعد أن أثبتت هذه الأخيرة محدودية آلياتها في الحفاظ على التوازنات المالية لدولة، وذلك بسبب الوتيرة العالية للإنفاق العمومي المتزامنة مع الانخفاض الحاد في أسعار النفط منذ النصف الثاني من سنة 2014. وعليه يتوجب على الجزائر توفير متطلبات إدراج الصكوك الإسلامية التي أثبتت نجاعتها في العديد من الدول الإسلامية، حيث يمكن استخدامها كبديل تمويلي للحفاظ على التوازن المالي للدولة والتخفيف من عجز موازنتها، وجذب شريحة واسعة من المستثمرين التي تأبى التعامل والتوظيف بفائدة معلومة مسبقا.
Keywords: الاقتصاد الإسلامي -- الصكوك الإسلامية -- الجزائر -- الموازنة العامة -- العجز المالي